Arab Spring - Hossain, Ishtiaq (The Oxford University Press, 2014)
This chapter, first of all, defines the term "Arab Spring". Then it provides a brief historical background to the Arab Spring. Having done these, the chapter subsequently analyses the following:Leadership and Organizational Structure; Evolution and Major Transformations; Impact on Political Dynamics and Future Prospects